The role of cytoskeleton and adhesion proteins in the resistance to photodynamic therapy: possible therapeutic interventions - Di Venosa, Gabriela Mariana (2015)
It is known that Photodynamic Therapy (PDT) induces changes in the cytoskeleton, the cell shape, and the adhesion properties of tumour cells. In addition, these targets have also been demonstrated to be involved in the development of PDT resistance. The reversal of PDT resistance by manipulating the cell adhesion process to substrata has been out of reach. Even though the existence of cell adhesion-mediated PDT resistance has not been reported so far, it cannot be ruled out. In addition to its impact on the apoptotic response to photodamage, the cytoskeleton alterations are thought to be associated with the processes of metastasis and invasion after PDT. In this review, we will address the impact of photodamage on the microfilament and microtubule cytoskeleton components and its regulators on PDT-treated cells as well as on cell adhesion. We will also summarise the impact of PDT on the surviving and resistant cells and their metastatic potential. Possible strategies aimed at taking advantage of the changes induced by PDT on actin, tubulin and cell adhesion proteins by targeting these molecules will also be discussed.